2013
DOI: 10.1007/s00586-013-3072-2
|View full text |Cite
|
Sign up to set email alerts
|

Selective estrogen receptor modulation prevents scoliotic curve progression: radiologic and histomorphometric study on a bipedal C57Bl6 mice model

Abstract: Purpose Previous work has suggested that progression of experimental scoliotic curves in pinealectomized chicken and bipedal C57BL6 mice models may be prevented and reversed with Tamoxifen treatment. Raloxifene is another Selective Estrogen Receptor Modulator (SERM) with estrogen agonist effects on bone and increases bone density but with fewer side effects on humans. To investigate whether scoliosis progression in bipedal C57Bl6 mice model could be prevented with SERM treatment and the mechanisms associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…In our study, the Triptorelin treatment reduced the incidence of scoliosis caused by estrogen. Our results on scoliosis rates in bipedal rat models differ from the results obtained by Demirkiran and colleagues 27 . The authors found that treatment with Tamoxifen (TMX) or Raloxifene (RLX) did not reduce the incidence of scoliosis, but TMX or RLX decreased the rate of progression of the deformity.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the Triptorelin treatment reduced the incidence of scoliosis caused by estrogen. Our results on scoliosis rates in bipedal rat models differ from the results obtained by Demirkiran and colleagues 27 . The authors found that treatment with Tamoxifen (TMX) or Raloxifene (RLX) did not reduce the incidence of scoliosis, but TMX or RLX decreased the rate of progression of the deformity.…”
Section: Discussioncontrasting
confidence: 99%
“…IS is the most common (84-89%) form of scoliosis and is frequently seen in young people and called adolescent IS [9]. The etiology or mechanism of scoliosis is not fully understood [2].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology or mechanism of scoliosis is not fully understood [2]. The most common etiopathogenesis of IS includes maturation disorders of the central and peripheral nervous system, connective tissue disorders in elastic and collagen fibers, muscle and bone diseases, platelet disorders, melatonin, hormone imbalances, genetic abnormalities, and leptin deficiency (essential in central nervous system development) [9][10][11]. Also, single nucleotide polymorphisms or any mutation related to ciliary functions and growth-regulating proteins may be related to IS development and progression [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Among other molecules involved in the melatonin signaling pathway, the role of estrogen receptors and CALM1 have attracted the attention of several investigators. Previous experimental studies have demonstrated that although selective estrogen receptor modulators, and CALM1 antagonists, do not prevent the occurrence of scoliotic deformities, they can decrease the rate of progression of the deformity in experimental animals (45)(46)(47). Conversely, replication studies and a meta-analysis did not confirm the previously suggested association between estrogen receptor gene polymorphisms and AIS predisposition or curve severity in humans (48)(49)(50)(51).…”
Section: Discussionmentioning
confidence: 83%